PENERAPAN MODEL PEMBELAJARAN QUANTUM LEARNING DAN ACTIVE LEARNING PADA MATERI LARUTAN PENYANGGA - Nasrulloh, Ahmad; Kusumo, Ersanghono (Chemistry in Education, 2015)
The purpose of this research is to know the comparasion between the students learning result taught by using cooperative learning based on quantum learning and active learning. The first experimental class was taught by using quantum learning model and the second class was taught by using active learning model. Both of quantum learning and active learning models are learning models that can trigger students to be active in teaching and learning process. The research design used was pre-test post-test group design and the sampling technique was purposive random sampling. The result of the last stage showed that the average of learning result of first experimental class was 75.71, whereas the second experimental class was 74.61. In collecting data, I used test, observation, and documentasion. The result of data analysis showed that quantum learning and active learning influence the chemistry student learning outcomes and quantum learning was not better than active learning.